Methods of Punishment in Education: Interpretation of the Prophet's Hadith with a Modern Educational and Educational Psychology Approach - Akbar, Raabiul; Zaenuri, Ahmad; Pratama, Irja Putra; Aristophan Firdaus (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Hadith holds a very important position in Islam, particularly as a way of life guide, including in educating children. However, there are still many instances of misinterpretation regarding hadiths related to the command to strike children, leading to incorrect interpretations. This study seeks to analyze the interpretation of the hadith concerning the command to strike children by using modern educational approaches and educational psychology. The research method is qualitative, supported by literature studies on both classical and modern texts. This study finds that the interpretation of the hadith about striking children for disciplinary purposes has been understood literally, without considering broader social, psychological, and pedagogical contexts. The study also finds that an educational approach emphasizing dialogue, understanding, and guidance is more effective in shaping the character and behavior of children. Based on these findings, a reinterpretation of the hadith is needed in a broader and deeper context of child education, integrating modern psychological and pedagogical values.